PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL PEMBELAJARAN IPS SISWA KELAS V SDN 010 RATUSIMA KECAMATAN DUMAI SELATAN - Saputra, Hendri Wandra Saputra Wandra; Alpusari, Mahmud Alpusari; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Education is the basic requirement for any nation, especially the nation of Indonesia that focuses on the development stage. One development is the field of education. Social science education (IPS) is one of the branches of the social sciences in mengaplikasiannya requires a special skill as a skill to be able to interact perfectly with the social world. The research was carried out at SDN 010 Ratusima of fifth grade students were 30 students and 12 students who completed only 18 students while not yet complete. It can be seen from the results of the daily tests fifth grade students which is still less than the KKM (Complete Minimal criteria). From the analysis of the data can be obtained prior to the implementation of this model is that there are students who get the KKM is 12 (40%) of students and KKM are under 18 (60%) students. In the first cycle increased to 22 (73.33%) and the second cycle to 27 (90.0%) orang.Dengan Thus, the results of the analysis of the action is in accordance with the hypothesis, the role-playing application of a model can improve the learning outcomes of students social studies class SDN 010 Ratusima Kecamatan Dumai Selatan, school year 2014/2015 has actually increased significantly. Keyword. Role Playing Model, Learning Outcomes IPS